Respuesta :

24a - 22 = -6(1-6a) equals a = - [tex] \frac{4}{3} [/tex]

First, expand. Your problem should look like: 24a - 22 = -6 + 36a.
Second, regroup terms. Your problem should look like: 24a - 22 = 36a - 6.
Third, subtract 24a from both sides. Your problem should look like: -22 = 36a - 6 - 24a.
Fourth, simplify 36a - 6 - 24a to 12a - 6. Your problem should look like: -22 = 12a - 6.
Fifth, add 6 to both sides. Your problem should look like: -22 + 6 = 12a.
Sixth, simplify -22 + 6 to -16. Your problem should look like: -16 = 12a.
Seventh, divide both sides by 12. Your problem should look like: [tex]- \frac{16}{12} [/tex] = a.
Eighth, simplify [tex] \frac{16}{12} [/tex] to [tex] \frac{4}{3} [/tex]. Your problem should look like: [tex] -\frac{4}{3} [/tex] = a.
Ninth, switch sides. Your problem should look like: a = [tex]- \frac{4}{3} [/tex] , which is your answer.